2016
DOI: 10.1152/ajprenal.00040.2016
|View full text |Cite
|
Sign up to set email alerts
|

The complement receptor C5aR1 contributes to renal damage but protects the heart in angiotensin II-induced hypertension

Abstract: Adaptive and innate immune responses contribute to hypertension and hypertensive end-organ damage. Here, we determined the role of anaphylatoxin C5a, a major inflammatory effector of the innate immune system that is generated in response to complement activation, in hypertensive end-organ damage. For this purpose, we assessed the phenotype of C5a receptor 1 (C5aR1)-deficient mice in ANG II-induced renal and cardiac injury. Expression of C5aR1 on infiltrating and resident renal as well as cardiac cells was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 35 publications
2
53
2
Order By: Relevance
“…In addition to the generation of autoimmunity, signaling through C5aR1 may also contribute to the perpetuation of nephritogenic autoimmunity that occurs in active disease after MPO deposition in the kidney, which is a site enriched for C5aR1-expressing APCs. 42 The production of ANCA is essential for the pathogenesis of AAV. We observed that MPO-ANCA titers were reduced in immunized C5aR1 À/À mice; this supports the role for the C5aR1 in promoting humoral immunity to other antigens seen in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the generation of autoimmunity, signaling through C5aR1 may also contribute to the perpetuation of nephritogenic autoimmunity that occurs in active disease after MPO deposition in the kidney, which is a site enriched for C5aR1-expressing APCs. 42 The production of ANCA is essential for the pathogenesis of AAV. We observed that MPO-ANCA titers were reduced in immunized C5aR1 À/À mice; this supports the role for the C5aR1 in promoting humoral immunity to other antigens seen in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these studies show that C5a-C5aR1 signalling is involved in renal disease initiation and progression via changes in mitochondrial agility, specifically through changes in cardiolipin remodelling, mitochondrial metabolite flux and mitochondrial respiratory function.Although the liver is the primary site of complement synthesis (40), local production of complement in the kidney, particularly within renal tubules could contribute to tissue injury in a variety of renal diseases(41). C5aR1 has been shown to be expressed on proximal tubular cells(42), podocytes(43), fibroblasts(44), mesangial cells, vascular endothelial and smooth muscle cells(11). Genome-wide transcriptome analysis showed upregulation of the complement pathway in microdissected human renal glomerular and tubule samples from patients with DKD(45).…”
mentioning
confidence: 99%
“…PMX53 treatment resulted in less ventricular collagen deposition and hypertrophy as compared with untreated hypertensive rats, whilst C5aR1 antagonism did not change systolic blood pressure (Iyer et al, 2011). We also found such a blood pressure-independent nephroprotective effect of C5aR1 deficiency in an accelerated model of hypertension in mice (Weiss et al, 2016). Moreover, using a C5aR1 reporter mouse in a hypertension model, expression of C5aR1 in the kidney was shown on dendritic cells as well as in monocytes/ macrophages and granulocytes.…”
Section: The Role Of Complement Activation Fragments In Hypertensionsupporting
confidence: 59%